PENGARUH PENGGUNAAN SMARTPHONE DAN PERGAULAN SOSIAL TERHADAP PERILAKU PESERTA DIDIK DI SMKN 5 TEBO - Puja Kesuma, Susanto (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
This research aims to examine the effect of smartphone usage and social interaction on the behavior of tenth-grade students at SMKN 5 Tebo. The study is grounded in the growing prevalence of smartphone usage among adolescents and the crucial role of social interaction in shaping individual behavior. A quantitative method with a descriptive approach was employed. The population consisted of 69 students, determined through a total sampling technique. The research instrument utilized was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using a partial t-test with the assistance of SPSS version 25. The findings indicate that smartphone usage does not exert a significant influence on student behavior (t calculated = 1.598 < t table = 1.997; sig. = 0.115 > 0.05). Conversely, social interaction demonstrates a positive and significant effect on student behavior (t calculated = 3.564 > t table = 1.997; sig. = 0.001 < 0.05). It is therefore concluded that social factors hold a more dominant role in shaping student behavior compared to smartphone use.